First record on the freshwater shrimp and its ecology in Weh Island, Indonesia - DEDI FAZRIANSYAH PUTRA; MUHAMMADAR ABDULLAH ABBAS; TONGKU NIZWAN SIREGAR; DAISY WOWOR (Society for Indonesian Biodiversity, 2025)
Abstract. Putra DF, Abbas MA, Siregar TN, Wowor D. 2025. First record on the freshwater shrimp and its ecology in Weh Island, Indonesia. Biodiversitas 26: 1991-2001. Freshwater ecosystems are important in term of biodiversity and the balance of life cycle in tropical regions. Freshwater shrimp is an important organism in its habitat, which play a crucial role in maintaining ecological balance and sustaining food chains. Weh Island, located at the tip of Sumatra Island, Indonesia, is very popular for its rich marine biodiversity, but unfortunately, studies on the ecology and the diversity of freshwater fauna in this island are very limited. Therefore, this is the first comprehensive study to report the identity, morphology, diversity, and ecological aspects of the freshwater shrimp. A total of 395 individuals of freshwater shrimp were collected from five sites of three different sampling localities namely Pria Laot Stream (lotic), Aneuk Laot Lake, and Paya Seunara Lake (lentic). Three species of freshwater shrimp of the genus Macrobrachium and one species of the genus Caridina were first reported from this island, i.e., Macrobrachium lar (TL: 2.9-9.6 cm; BW: from 0.21-15.67 g), M. lanatum (TL: 3.0-4.5 cm; BW: 0.29-1.71 g), M. lanchesteri (TL: 5.0-10 cm; BW: 0.1-1.1 cm), and Caridina serratirostris (TL: 1.6-2.8 cm; BW: 0.03-0.28 g). Pria Laot River showed low levels of shrimp diversity, moderate Dominance Index, and fairly high species evenness, while Aneuk Laot and Paya Seunara Lake indicated low levels of shrimp diversity and evenness but high Dominance Index by M. lanchesteri. Although Weh Island offers a unique ecological niche for freshwater shrimp, the increasing threats from human activities, deforestation, and climate change are very real. There is a need for effective actions and prevention, which are essential for the protection of not only shrimp population but also the integrity of the entire terrestrial ecosystem. Collaborative efforts and synergy between local communities, government, and tourists are essential to implement sustainable strategies as a priceless legacy for future generations.